Ichthyosaurian palaeopathology: evidence of injury and disease in fossil 'fish lizards' - Pardo Perez, Judith Mariana; Kear, B. P.; Gomez, M.; Moroni, M.; Maxwell, E. E. (My University, 2018)
The documented record of ichthyosaurian paleopathologies reveals an array of injury-related bone modifications and instances of disease evidenced through multiple clades, skeletal regions and body-size classes from the Middle Triassic to middle Cretaceous. Examples include traumatic injuries, as well as a high incidence of articular diseases, including avascular necrosis. Forelimb pathologies are particularly abundant (65% of total reported), and the glenoid region seems to have been especially prone to articular disease. In contrast, pathologies affecting the vertebral column are comparatively underrepresented (6% of reported pathologies). Also notable is the disproportionate commonality of osteopathologies in ichthyosaurian taxa between 2 and 6m in length (54%), as opposed to demonstrably larger (31%) or smaller bodied (15%) species. Furthermore, osteopathologies are almost exclusively described from skeletally mature individuals, and are best known from taxa of Jurassic age (78%), versus those from the Triassic (15%) or Cretaceous (7%); this likely reflects biases in the ichthyosaurian fossil record through time. Ichthyosaurs evince remarkable similarities in the types of observed skeletal damage relative to other ecologically similar marine amniotes - especially cetaceans and mosasaurid squamates, all of which potentially exhibited equivalent palaeoecological and/or behavioural adaptations for life in aqueous environments. Notably, however, the unusually low frequency of vertebral pathologies in ichthyosaurs is peculiar, and requires further investigation to establish significance.
Keywords: palaeobiology; ichthyosauria; mesozoic; reptilia; avascular necrosis; osteotrauma; palaeopathology